Analysis of waterproofing defects and technology development for car parking roofs: Lithuanian case - Ustinovichius, Leonas; Rasiulis, Romas; Ignatavičius, Česlovas; Vilutienė, Tatjana (Journal of Civil Engineering and Management, 2012)
This work presents the analysis of installation options of exploitable car park roofs offered by the designers, material manufacturers and suppliers and introduces the Lithuanian legislation with the requirements for this type of roofing. Reasons of the most frequently occurring defects have been examined and several options for correcting defects have been provided. The most cost-effective option for correcting the defect in question has been chosen. Practical measures for increasing the reliability of exploitable car park roofs have been proposed. The analysis has shown that at a minimum slope reliability of the exploitable roof coated with roller heat-welded materials is not guaranteed. The authors propose to tighten the requirements on car park roofing.